The development of integrated palliative care and emergency medical services in South Africa - Gage, Caleb (Department of Medicine, 2025)
Background The role of Emergency Medical Services in out-of-hospital patient management has evolved rapidly in recent years to include more intricate and integrated forms of healthcare beyond emergency care. For example, there has recently been recognition of the role Emergency Medical Services play in the provision of palliative care. The developing body of literature on this topic has recommended Emergency Medical Services and palliative care systems should integrate to improve palliative situation management in the out-of-hospital setting. In South Africa, however, these systems remain segregated. As a result, palliative situations are managed poorly by Emergency Medical Services providers due to disregard of patient autonomy and performance of aggressive, futile interventions. Potential benefits of integration between these systems include delivery of early palliative care, provision of home-based care, respect of patient autonomy, improved patient/family quality of life, increased patient and family satisfaction and confidence, decreased health care costs and appropriate trajectories of care. A further benefit in the low-to-middle income context of South Africa would be efficient use of limited resources. Aim and Objectives To develop a framework for the integration of palliative care and Emergency Medical Services systems in South Africa. The research aim was pursued through the following objectives, each of which represented a study within the thesis: Study 1: To review existing literature concerning the intersection of palliative care and Emergency Medical Services. Study 2: To examine Emergency Medical Services use for palliative situations in South Africa. Study 3: To gather the perspectives of palliative care providers on Emergency Medical Services use in palliative care in South Africa. Study 4: To gather perspectives of South African patients and family members with palliative needs concerning Emergency Medical Services use in their care. Study 5: To develop and prioritise approaches facilitating Emergency Medical Services and palliative care system integration within South Africa. Methods Study 1 was a scoping literature review performed with an a priori search strategy inclusive of grey literature. Empirical, English studies involving human populations published between 1 January 2000 and 24 November 2022 concerning EMS and palliative care were included. Extracted data underwent descriptive content analysis. Study 2 was an observational, descriptive, retrospective patient record review employed at two hospitals with palliative care services in the Western Cape of South Africa. All patient records of those who arrived at the hospitals between 1 January 2020 and 31 December 2020 via EMS conveyance leading to palliative care provision were included in the study. Summary descriptive statistics (medians, ranges) were used to describe the numerical data (such as patient age). Clinical variables (such as patient chief complaint) were analysed as categorical data. Emergency Medical Services intersection with palliative situations according to time of day, working hours, day of week, and month of year were subjected to Chi-squared testing for temporal analysis. Geospatial data were investigated using cluster and proximity analyses. Spatio-temporal and clinical analyses were reported in separate articles. Study 3 employed a qualitative design using individual semi-structured interviews with doctors and nurses holding post-graduate palliative medicine qualifications. Verbatim transcriptions of interviews were subjected to content analysis using an inductive-dominant approach to develop codes and categories. Study 4 employed a qualitative design using individual semi-structured interviews with patients and family members with palliative needs. Verbatim transcriptions of interviews were subjected to thematic analysis using an inductive-dominant approach to develop categories and themes. Study 5 was a nominal group technique, involving experts from both Emergency Medical Services and palliative care, who answered the question “what do you think should be done to most effectively integrate Emergency Medical Services and palliative care services in South Africa?” Answers were sorted into categories, awarded scores by participants, and ranked according to their impact and feasibility within SA. Interviews with Emergency Medical Services providers were performed previously and are not repeated in this thesis. However, findings from this previous study are incorporated. Results Study 1 included 56 articles for review. Overall, these articles noted that EMS have a role to play in out-of-hospital palliative care, however, many challenges must be overcome. This study identified knowledge gaps and provided overall context for the thesis and subsequent studies. In Study 2, 1 207 unique patients received palliative care services during the study period. Of these, 395 (33%) made use of Emergency Medical Services for hospital conveyance on 494 occasions. The median (range) patient age was 60 (20-93) years, and most transports involved male patients (54%, n=265). Family members were the primary caregivers in most instances (89%, n=440), dyspnoea was the most common chief complaint (36%, n=178) and cancer was the most frequent diagnosis (32%, n=159). The median length of hospital stay was 6 days, with most patients discharged home (60%, n=295). Most Emergency Medical Services transports occurred from peri-urban areas (78%, n=385), during the daytime (52%, n=257), out-of-office hours (53%, n=261), and weekdays (76%, n=375). Statistically significant variation in distribution was found according to time of day (p=<0.001), with 38% (n=188) of cases occurring between 13h00 and 19h00, and month of year (p=<0.001), with 36% (n=177) occurring in June, August and October. Proximity analysis revealed a mean driving time of 6.69min and distance of 3.65km to palliative care facilities. This study provided quantitative evidence of Emergency Medical Services intersection with palliative situations in South Africa as well as insight into palliative care access. Study 3 found that palliative care providers maintained an overall positive view of integration with Emergency Medical Services, noting their beneficial impact and suggesting various methods of integration, while also highlighting challenges and concerns. In Study 4 patients and family members with palliative care needs described a loss of previous control they held over their lives and a subsequent longing to maintain what control remained. Emergency Medical Services care was viewed positively when this longing was satisfied and negatively when further control was seized. These studies allowed for the incorporation of primary stakeholder perspectives on the integration of Emergency Medical Services and palliative care. In Study 5, fifty-two methods of Emergency Medical Services and palliative care integration were generated and ranked by the expert panel. These methods formed the following categories (listed in rank order from highest to lowest): Awareness, Education, Community Engagement, Communication and Information Sharing, Stakeholder Collaborations, Alternative Pathways and Approaches, Research, Funding, Policy Development, Governance. Conclusions This thesis identified and filled knowledge gaps concerning Emergency Medical Services and palliative care integration in the South African setting through review of contemporary literature, retrospective analysis of palliative situations involving Emergency Medical Services, gathering of primary stakeholder views, and expert panel development of integrative methods. While previously assumed, substantial intersection between Emergency Medical Services and palliative situations in South Africa has now been demonstrated, highlighting the significance of this topic within the country. Primary stakeholder perspectives offered support for Emergency Medical Services and palliative care integration, and novel insights into patient and family member experiences, necessitating a person-centred approach to care, have been provided. Guidance for the implementation of such integration, provided by experts from both Emergency Medical Services and palliative care systems, has been developed. Based on this evidence, a conceptual framework for Emergency Medical Services and palliative care integration in South Africa was produced alongside guidance for practical use. The implementation of this framework will assist in the efficient use of limited healthcare resources in the country while simultaneously improving access to and quality of palliative care for those in need. Though the framework presented here was developed for the South African context, it contains elements from the international literature as well as World Health Organization and health system integration frameworks. Thus, this framework may have applications outside of South Africa, particularly in other low-to-middle income countries with similar resource constraints. Future research should monitor the safety and efficacy of framework implementation, investigate the economic impact of EMS and palliative care integration through cost effectiveness studies, develop curriculum for EMS education in palliative care, and involve pilot studies.